Crime and punishment: A realistic group conflict approach to racial discrimination in hiring convicted felons. Issue 1 (11th February 2019) - Goldman, Barry; Cooper, Dylan; Kugler, Tamar
Abstract : Purpose: A surprisingly large proportion of the working population of the USA consists of individuals with felony convictions. Moreover, the issue of employability of these individuals is compounded for minorities. This paper aims to present two experimental studies investigating whether minorities with felony backgrounds have a more difficult time being selected for employment than identically situated white applicants. The authors ground the paper in realistic group conflict theory. Results indicate discrimination is more acute against minorities with felony backgrounds than whites with the same background and shed light on the mechanisms leading to this discrimination. Theoretical and practical implications are discussed. Design/methodology/approach: This paper involves two experimental studies involving working adults engaging with realistic survey situations using mTurk. Findings: Results of both studies indicate discrimination is more acute against minorities with felony backgrounds than whites with the same background, and shed light on the mechanisms leading to this discrimination. Research limitations/implications: One limitation of the methodology is that the authors used fictional candidates and jobs. This may have led to understating the effects of discrimination on minorities because it allowed applicants to answer in socially desirable ways (e.g. absent of racial bias) without suffering any of the anticipated negative consequences of actually hiring individuals about whom they hold negative stereotypes. Practical implications: This research has several important implications for practice. First, organizations should be keenly aware of the potential for subtle and unconscious bias to affect the job application process even among well-intentioned hiring managers. Second, as the bias is often triggered by threats, organizations should share with their employees the nature of the threat involved with former felons. Social implications: Organizations should deliberately address issues associated with the use of criminal background checks. For many organizations, a felony conviction in an applicant's background automatically eliminates that person from employment. However, a substantial amount of the workforce now has a felony in their background. Indeed, the Equal Employment Opportunity Commission (2012 ) has issued guidelines that detail important factors that organizations should consider on a case-by-case basis when considering employment for former felons. Organizations may consider updating any blanket exclusions regarding the hiring of ex-felons – not only because it makes good policy but also because it may help the organization hire the best people. Originality/value: This research studies an important – and growing – societal problem related to the hiring of convicted felons, and the related issue of racial discrimination that affects black convicted felons particularly hard. There has been very little work in the management area on this topic. Moreover, there has been very little work in all areas that includes experimental methods. The use of such methods is particularly useful to eliminate confounds found in field data.